TGM Discussion with Ágnes Heller and István Mészáros - What's Left of Marx?
Recording of a discussion, part of a public debate series entitled "Controversies" moderated by CEU Visiting Professor Tamás Gáspár Miklós. This is the recording of the first event of this kind, held on March 21, 2001. The debate on "What's Left of Marx?" was between Ágnes Heller of New School University and István Mészáros of the University of Sussex.